2012
DOI: 10.1007/s13670-012-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Traumatic Brain Injury in China

Abstract: Traumatic brain injury (TBI) is one of the major causes of morbidity and mortality in China. The elderly population has the higher rates of TBI-related hospitalization and death. Traffic accidents are the major cause for TBI in all age groups except in the group of 75 years and older, in which stumbles occurred in nearly half of those who suffered TBI. Older age is known to negatively influence outcome after TBI. To date, investigators have identified a panel of prognostic factors that include initial Glasgow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The prevalence of serious head injury and/or being knocked unconscious or reporting only a concussion ranged from 25.9% to 10.1% in BMHS participants aged 50+ years and this broadly concurs with other studies from China [ 23 ] and Australia [ 24 ] which reported prevalence rates of around 19% and 24.1% of TBI and concussion, respectively, but our rates are lower than the 45% reported in a UK cohort of older trauma patients [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of serious head injury and/or being knocked unconscious or reporting only a concussion ranged from 25.9% to 10.1% in BMHS participants aged 50+ years and this broadly concurs with other studies from China [ 23 ] and Australia [ 24 ] which reported prevalence rates of around 19% and 24.1% of TBI and concussion, respectively, but our rates are lower than the 45% reported in a UK cohort of older trauma patients [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the literature, some studies report that male patients more frequently present with TBI in all age groups, whereas some other studies report that the frequency of female patients is higher. [17][18][19] According to our data, the most common reason for TBI in admitted patients was falling from the same level (76%). This is in accordance with previous reports, whereas one of the least common causes of TBI was motor vehicle collisions.…”
Section: Discussionmentioning
confidence: 61%
“…35 Results of our study mirror worldwide trends in developed countries where visits to the ED, inpatient hospitalizations, and mortalities from TBI are increasing in older adults, but are stable or decreasing in other age groups, even accounting for population shifts. These trends are demonstrated in numerous international studies from Australia, 36 Austria, 37 Canada, [38][39][40] China, 41,42 Finland, [43][44][45] Germany, 46 Great Britain, 47 Japan, 48 the Netherlands, 49 Scotland, 50 Spain, 43,51 and the United States. 52 Trends in less developed countries are harder to assess.…”
Section: Discussionmentioning
confidence: 93%